Compositional, Nutritional, and Functional Characteristics of Instant Teas Produced from Low- and High-Quality Black Teas - Alasalvar, Cesarettin; Pelvan, Ebru; Ozdemir, Kubra Sultan; Kocadagli, Tolgahan; Mogol, Burce Atac; Pasli, Ayca Ayfer; Ozcan, Nihat; Ozcelik, Beraat; Gokmen, Vural (American Chemical Society (ACS), 2013)
Two types of instant teas produced from low- and high-quality black teas were examined for their proximate composition, dietary fiber, minerals, water-soluble vitamins, total phenolic content, various antioxidant assays, phenolics (flavanols, condensed phenolics, and phenolic acids), alkaloids, and carotenoids as well as taste-active compounds (sugars, organic acids, and free amino acids). Some variations, albeit to different extents, were observed (p < 0.05) among these parameters between instant teas produced from low- and high-quality black teas. With respect to proximate composition, carbohydrate was the predominant component (56.68-59.84 g/100 g), followed by protein (19.31-19.86 g/100 g). Ash, moisture, and, to a lesser extent, dietary fiber and fat were also present in both instant teas. Thirteen minerals, four water-soluble vitamins, six flavanols, two alkaloids, three condensed phenolics, one phenolic acid, and one carotenoid were identified. Total phenolic content varied between 17.35 and 17.82 g of gallic acid equivalents (GAE)/100 g instant tea. With regard to antioxidant activities, three different assays such as oxygen radical absorbance capacity (ORAC), trolox equivalent antioxidant capacity (TEAC), and cupric ion reducing antioxidant capacity (CUPRAC) were measured. No significant differences (p > 0.05) in total phenolic, ORAC, TEAC, and CUPRAC contents between low- and high-quality instant teas were observed. With regard to taste-active compounds, 3 sugars, 5 organic acids, and 18 free amino acids were positively identified, of which fructose, tannic acid, and theanine predominated, respectively. The present work suggests that despite some differences, instant teas produced from low- and high-quality black teas should not be distinguished on the basis of their compositional, nutritional, and functional characteristics as well as taste-active compounds.
Keywords: Dietary Fiber; Flavonoids; Quality Control; Phenols; Tea; Plant Extracts; Nutritive Value; Antioxidants; Camellia sinensis